Hydronephrosis Associated with Cervical Cancer Case Report on Pathophysiology, Diagnosis, and Management - Stolarek, Kacper; Kowalczyk, Emilia; Szarek, Mateusz; Andrzejak, Alicja; Olszewski, Hubert (Quality in Sport, 2024)
Introduction and Purpose Cervical cancer is one of the most common malignancies in women, accounting for the fourth most common cancer worldwide and the sixth in Poland. Despite advances in diagnosis and prevention, the condition is still associated with a high mortality rate, especially in advanced stages. One of the significant complications of advanced cervical cancer is hydronephrosis, occurring in about 23% of patients. Hydronephrosis develops as a result of blocked urine outflow, which leads to stretching of the renal calyces and can result in renal failure if not properly treated. Management strategies for hydronephrosis include ureteral stenting and percutaneous nephrostomy, both of which are effective in draining the kidneys and improving patient outcomes. Aim of the study This article discusses the pathophysiology, diagnosis and treatment of hydronephrosis in patients with cervical cancer, and presents a detailed case report of a patient with advanced cervical cancer complicated by hydronephrosis and renal perforation. Results and Future directions The patient was admitted to the urology department for bleeding into the retroperitoneal space after renal fistula replacement. During hospitalization, despite numerous complications, the patient’s condition stabilized after blood and plasma transfusions, intensive antibiotic therapy and renal fistula re-implantation. The final results of the treatment were successful, and the patient was discharged with appropriate recommendations. The study highlights the importance of early diagnosis and effective treatment of hydronephrosis to improve the prognosis of patients with cervical cancer. It underscores the need for multidisciplinary collaboration involving urologists, oncologists and other specialists to provide comprehensive care tailored to the patient’s evolving needs.